La formación profesional en España en el marco de la implantación de la enseñanza secundaria obligatoria: el contraste con el modelo Belga - González Hern´andez, Ángel; Ayala De La Peña, Amalia (Revista Española de Pedagogía, 2025)
In this article the vocational education systems in Spain and Belgium are compared as a means to offer some insights into the role that vocational education plays in the context of a country’s offer of secondary education. It follows from the comparison that the current Spanish reform has not taken into account the implications of the particular relations that often are established between the general and vocational tracks of the education system, benefiting thus from the experiences of other countries, namely the case of the Belgian reformed system.